2010
DOI: 10.1115/1.4001659
|View full text |Cite
|
Sign up to set email alerts
|

On the Buckling of Functionally Graded Cylindrical Shells Under Combined External Pressure and Axial Compression

Abstract: The stability problem of a circular cylindrical shell composed of functionally graded materials with elasticity modulus varying continuously in the thickness direction under combined external pressure and axial compression loads is studied in this paper. The formulation is based on the first-order shear deformation theory. A load interaction parameter is defined to express the combination of applied axial compression and external pressure. The stability equations are derived by the adjacent equilibrium criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…Table 3. These values were taken from the study of Khazaeinejad et al [36]. Table 3 shows that there are good agreements between the present results in the framework of the SDT and the results of Khazaeinejad et al [36].…”
Section: Convergence Studysupporting
confidence: 72%
See 1 more Smart Citation
“…Table 3. These values were taken from the study of Khazaeinejad et al [36]. Table 3 shows that there are good agreements between the present results in the framework of the SDT and the results of Khazaeinejad et al [36].…”
Section: Convergence Studysupporting
confidence: 72%
“…Shen [35] presented a study on the postbuckling response of a shear deformable functionally graded cylindrical shell of finite length embedded in a large outer elastic medium and subjected to axial compressive loads in thermal environments. Khazaeinejad et al [36] investigated the buckling of functionally graded cylindrical shells under combined external pressure and axial compression on the basis of SDT. Lang and Tran et al [37] analyzed isogeometric of functionally graded plates using higher-order shear deformation theory.…”
Section: Introductionmentioning
confidence: 99%
“…By using Equations (6), (9), (11), and (12), we obtain the expressions for force, moment, and strain components in the reference surface, which are then substituted in the stability and compatibility equations [45,47] to obtain the following governing differential equations for FG-CNTRC-CSs under a CL, with independent parameters Φ, w, ϕ 1 , ϕ 2 , i.e.,…”
Section: The Governing Equationsmentioning
confidence: 99%
“…In many engineering and building structures, shells are subjected to a simultaneous action of different loads, such as a combined compressive force and external pressure, which can affect significantly their global stability, as observed in the pioneering works [1][2][3][4][5], within a parametric study of the buckling response for homogeneous composite cylindrical and conical shells subjected to a combined loading (CL). Among the novel class of composite functionally graded materials (FGMs), the first studies on the buckling response of FGM-based shells subjected to a CL can be found in [6] and [7], for cylindrical and conical shells, as well as in [8][9][10][11][12][13][14] for different shell geometries and boundary conditions, while considering different theoretical approaches. Moreover, the increased development of nanotechnology has induced a large adoption of nano-scale materials, e.g., CNTs, in many engineering systems and devices, discovered experimentally by Iijima [15] in 1991 during the production of fullerene by arc discharge evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the investigation of buckling of cylindrical FGMs shells is a necessary fundamental problem, which has attracted attention of many researchers. Khazaeinejad [13] …”
Section: Introductionmentioning
confidence: 99%